Biologics for treating axial spondyloarthritis. (3rd June 2018) - Jones, Alexis; Ciurtin, Coziana; Ismajli, Mediola; Leandro, Maria; Sengupta, Raj; Machado, Pedro M.
ABSTRACT: Introduction : Spondyloarthritis (SpA) encompasses a heterogeneous group of diseases sharing genetic, immunological, clinical and imaging features. Axial spondyloarthritis (axSpA) refers to a subgroup characterised predominately by inflammation of the axial skeleton with subsequent symptoms of chronic (often inflammatory) back pain and sacroiliitis. There is a strong association with the major histocompatibility complex (MHC) class I allele human leukocyte antigen (HLA) B27. In the last decade, there has been significant progress in earlier detection of the disease and the molecular mechanisms involved in its pathogenesis. The subsequent introduction of anti-tumour necrosis factor (TNF) has revolutionised the treatment of patients with axSpA. Areas covered : In this article, we review the current biologic therapies for axSpA, the emergence of biosimilars, predictors of response, primary and secondary failure and new biologics on the horizon. Expert opinion : There have been significant advances in the treatment of axSpA. Beyond the clear efficacy of anti-TNF inhibition, IL-17 offers an alternative therapeutic target and there is promise from inhibition of the IL-17/IL-23 pathway and small molecules, such as Janus kinase (JAK) inhibitors. Biosimilars have offered greater affordability and choice within this increasingly growing field of therapeutics.